Managing different types of innovation: mutually reinforcing management control systems and the generation of dynamic tension. Issue 3 (16th April 2017) - Curtis, Emer; Sweeney, Breda
Abstract : Using a single case study of a highly innovative medical device company engaged in two types of innovation (technological and customer-oriented), this paper examines the nature of the relationship between mutually reinforcing management control systems (MCSs) and the generation of dynamic tension between the different types of innovation. Findings show how mutually reinforcing MCSs create a push for consistency but fail to generate a dynamic tension between different types of innovation, thus crowding out one type of innovation. While the literature to date has been unclear on how mutual reinforcement and the generation of dynamic tension are related, this study makes a distinction between mutually reinforcing control systems that support each other in driving momentum around a particular strategic objective (consistent reinforcement), and control systems which are reinforcing in creating dynamic tension, thus reducing momentum in one particular direction (countervailing reinforcement). It also contributes to the literature by highlighting the protective role that MCSs can play in the management of innovation. Feedback and measurement systems reduce the vulnerability of resources to diversion to other areas by stimulating action on projects, driving accountability around the use of the resources, and commanding management attention.